(untitled) (Research, Society and Development, 2021)
The significant expansion of the forestry sector in Brazil has given evidence to studies that direct its research actions towards the preservation and rational use of natural resources. Research has shown that changes in land use alter its pedoenvironmental conditions. Therefore, the present study aimed to investigate long-term anthropic actions on the Pampa biome area in Rio Grande do Sul: Effect on physical properties of soil with substitution of use under natural pasture for use of commercial forestation of Eucalyptus spp. Samples of an Ultisol (Argissolo Vermelho Distrófico, SiBCS) were collected in a planted forest, in triplicate and at five depths, and a control soil, vegetated with a natural pasture, was also collected. There was no change in the particle size distribution of the soil. After 17 years of forestation, an increase in the hematite content was observed in the forest bulk soil and the rhizospheric soil, an increase in the values of magnetic susceptibility and a decrease in the specific surface area of the particles in depth.